Public Education and Economic Competitiveness - Gabriel-Andrei Donici (CES Working Papers, 2011)
There is a certain connection between education and economic competitiveness. The relation between these two concepts is easy to intuit. On the medium and long term investments in education generate a strong increase in a country's level of economic competitiveness. Through education the human capital is formed, and it affects all economic fields. Therefore we can observe that human capital has a decisive influence on the economic competitiveness of a country.
Keywords: E24; H23; H41; 330; Investments; education; economic competitiveness; public goods Romania